2018
DOI: 10.14581/jer.18005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Seizure-Related Injuries in an Epilepsy Cohort from North India

Abstract: Background and PurposeTo identify predictors of seizure-related injury (SRI) and death in people with epilepsy (PWE) in a North Indian cohort.MethodsThis ambispective cohort study included PWE registered in an epilepsy clinic in Delhi between May 2010 and December 2011. Five hundred twenty-six patients were enrolled and followed for 25 months. Patients were categorized into two groups based on SRI/no SRI during the study period. We analyzed various factors to identify predictors of SRI and death.ResultsOf 526 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In a study conducted by Russell-Jones et al, after analyzing 12,626 epileptic seizures associated with falls, the researchers found only one confirmed skull fracture, one subdural hematoma, and one epidural hematoma [22]. In a study from North India, only two hematomas requiring surgical evacuation were noted in a population of 171 patients with seizure-related injuries [23]. A 2-year longitudinal study of seizure-related injuries in a population of epilepsy patients at the Baylor Comprehensive Epilepsy Center in Houston, TX, USA showed that severe head injuries are rare, and out of 306 studied patients, only one had an intracranial hematoma requiring neurosurgical intervention, and no skull fracture was reported [24].…”
Section: Consequencesmentioning
confidence: 99%
“…In a study conducted by Russell-Jones et al, after analyzing 12,626 epileptic seizures associated with falls, the researchers found only one confirmed skull fracture, one subdural hematoma, and one epidural hematoma [22]. In a study from North India, only two hematomas requiring surgical evacuation were noted in a population of 171 patients with seizure-related injuries [23]. A 2-year longitudinal study of seizure-related injuries in a population of epilepsy patients at the Baylor Comprehensive Epilepsy Center in Houston, TX, USA showed that severe head injuries are rare, and out of 306 studied patients, only one had an intracranial hematoma requiring neurosurgical intervention, and no skull fracture was reported [24].…”
Section: Consequencesmentioning
confidence: 99%
“…Given the diagnostic challenges associated with respiratory dysfunction in epileptic encephalopathies, comprehensive respiratory assessments are crucial. These assessments should be tailored to the individual's clinical presentation and history, including the type and frequency of seizures, cognitive function, and sleep patterns [ 23 ]. Polysomnography (PSG) is a valuable tool for assessing sleep-related respiratory disturbances, including apneas, hypoventilation, and irregular breathing.…”
Section: Reviewmentioning
confidence: 99%
“…Epilepsy is a chronic condition, but a subset of patients in this group have multiple seizures daily [ 14 ]. Risks of continuing seizures include unexpected injuries, epileptic encephalopathy, status epilepticus, side effects of anti-epileptic drugs (AEDs), and the cumulative risk of sudden unexpected death in epilepsy patients [ 8 , 10 , 14 ]. This assumes more importance in a child suffering with daily seizures, especially when evaluation reveals a condition which may be amenable to surgical correction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%